MAIN CHARACTERISTICS OF PERSONAL ACTIVITY OF GOVERNOR AND LEADER (Intent Research Scientific Journal, 2023)
The leader's personality and work activity is a creative process that ensures management efficiency. In the history of management, the problem of the leader and the governor is a result that covers such important issues as achievements in management, personal activity of the leader, personnel potential, management efficiency, and represents the development or decline in the socio-political, economic, spiritual and cultural spheres of a certain period. served as a quality and efficiency factor. In the article, the practical activities of the leader and the leader in the process of management and the results of their work, general actions, the set goal and the mechanisms of its implementation, the characteristics of the leader and the leader in management, the creative thinking of the leader, and some considerations are given.